Preparation of Furfural From Xylose Catalyzed by Diimidazole Hexafluorophosphate in Microwave - Huang, Ting; Yuan, Kun; Nie, Xu-Liang; Chen, Jing; Zhang, Huang-Xian; Chen, Jin-Zhu; Xiong, Wan-Ming (Frontiers in Chemistry, 2021)
In this work, functionalized alkyl imidazolium hexafluorophosphate ILs were synthesized and characterized; then, they were applied in the conversion of xylose to furfural under the microwave method. The results showed that when CnMF was used as a catalyst, an acidic environment was provided to promote the formation of furfural. In addition, the heating method, the solvent, and the different structures of cations in the ionic liquid influenced their catalytic activity. In an aqueous solution, the yield of furfural obtained using the microwave method was better than that of the conventional heating method, and the catalytic activity of diimidazole hexafluorophosphate was better than that of monoimidazole. Meanwhile, for the diimidazole hexafluorophosphate, the change of the carbon chain length between the imidazole rings also slightly influenced the yield. Finally, the optimal yield of 49.76% was obtained at 205°C for 8 min using 3,3′-methylenebis(1-methyl-1H-imidazol-3-ium), C1MF, as a catalyst. Mechanistic studies suggested that the catalytic activity of C1MF was mainly due to the combined effect of POFn (OH)3-n and imidazole ring. Without a doubt, the catalytic activity of C1MF was still available after five cycles, which not only showed its excellent catalytic activity in catalyzing the xylose to prepare the biomass platform compound furfural but also could promote the application of functionalized ionic liquids.